2002
DOI: 10.1136/sti.78.3.166
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection among Chinese residents in the United Kingdom

Abstract: Objective: To determine prevalence of hepatitis B virus (HBV) serological markers in Chinese residents in the United Kingdom. Method: Retrospective case-controlled study between January 1997 and June 2000 in two genitourinary medicine (GUM) clinics. Results: 117 Chinese and 234 non-Chinese controls were studied. Baseline characteristics except marital status showed no difference. Overall prevalence of HBV serological markers was 35.8% in Chinese, controls 5.5% (p<0.001). Hepatitis B surface antigen (HBsAg) pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 17 publications
1
26
0
1
Order By: Relevance
“…In Chinese and Asian women, the carrier rate is up to 20% (8)(9)(10). In our hospital, the annual obstetric statistics indicated that up to 2007, the prevalence of HBV was still 10%.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In Chinese and Asian women, the carrier rate is up to 20% (8)(9)(10). In our hospital, the annual obstetric statistics indicated that up to 2007, the prevalence of HBV was still 10%.…”
Section: Discussionmentioning
confidence: 92%
“…In Hong Kong and China and among the Asian immigrant population in Australia or New Zealand as well as Chinese women in the United Kingdom, the prevalence of HBV is up to 20% (8)(9)(10). It is possible among populations with a high prevalence that HBV infection may be an unrecognized cause of subfertility and also affects the outcome of IVF and embryo transfer treatment.…”
mentioning
confidence: 94%
“…It should be highlighted that many represented adopted immigrant children from Asia, where HBV is hyperendemic and vaccine prophylaxis programs in childhood are often not done [Lavanchy, 2004]. Several reports have underlined the high prevalence of HBV in immigrants can modify the declining trend of HBV infection in Western countries [Kawsar and Goh, 2002;Gjorup et al, 2003;Scotto et al, 2005]. In contrast to Africans and Asians, Latin Americans showed a low prevalence of HBV markers in the study population.…”
Section: Sequence Accession Numbersmentioning
confidence: 92%
“…10 A 2013 UK study demonstrated that 1.1% of tested individuals were positive for HBsAg; 11 in 2009, the prevalence of HBV among migrants in the UK was estimated to be 4%, 12 ranging from 0.1% to 17.4% depending on ethnic group and study method. [13][14][15][16][17][18] In 2012, the National Institute for Health and Care Excellence (NICE) recommended that all people born in a country with HBV prevalence of ≥2% should be offered a HBV test and that testing is offered in primary care. 19 In 2011, approximately 7.5 million (13%) individuals living in England and Wales were born outside of the UK.…”
Section: Introductionmentioning
confidence: 99%